Intelligent network video : understanding modern video surveillance systems - Nilsson, Fredrik (CRC Press, 2009)
"Offering ready access to the security industry's cutting-edge digital future, Intelligent Network Video provides the first complete reference for all those involved with developing, implementing, and maintaining the latest surveillance systems. Fredrik Nilsson explains how IP-based video surveillance systems provide better image quality, and a more scalable and flexible system at lower cost."--BOOK JACKET.